How can we improve the quality of transplantable lungs?. (1st November 2016) - Levin, Kovi; Kotecha, Sakhee; Westall, Glen; Snell, Gregory
ABSTRACT: Introduction : Optimization of lungs for organ donation is becoming increasingly important as donation rates stagnate despite growing waiting lists. Improving procurement and utilization of donated lungs has the ability to reduce mortality and time on the lung transplantation (LTx) waiting list. Additionally, assessment and optimization of donor lungs can reduce both early and late post-LTx morbidity and mortality, as well as reduce overall costs and resource utility. Areas covered : Strategies that we will discuss in detail include intensive care management practices, such as targeted ventilation protocols and therapeutic bronchoscopy, as well as the ever expanding possibilities within the arena of ex vivo lung perfusion (EVLP). Expert commentary : Donor lung quality is currently optimized both in vivo prior to organ procurement, and also via EVLP circuits. Despite good evidence demonstrating the utility of both approaches, data remain elusive as to whether EVLP is beneficial for all donor lungs prior to implantation, or instead as a tool by which we can evaluate and recondition sub-optimal donor lungs.